Strategy of Heritage Tourism Development in Surakarta, Central Java – Indonesia - Karnowahadi, Karnowahadi (RSF Conference Series: Business, Management and Social Sciences, 2025)
Surakarta is a city that has different types of heritage, either in the form of buildings, handicraft products, culinary, and religious events. The heritage is a tremendous asset and must be preserved. Preservation of heritage is costly. Aside from the government budget sources, the cost of preserving heritage requires the participation of the community. So, that requires the government policy in the preservation of heritage. This study aimed to analyze the socio-economic and tourist behavior, and analyze the strategy of heritage tourism development in Surakarta. Findings from this study are: first, heritage tourism development is influenced by several factors, including WTP, gender, age, level of least visited, type of job, income, education, status, and region of origin. Secondly, Surakarta has a huge potential to develop tourism based on its heritage. The development strategy is to optimize the performance of the government, cooperating with stakeholders, to motivate people to actively participate in funding the preservation of heritage, as well as managing the budget more transparently and accountably.